Characteristics of patients with sudden onset sensorineural hearing loss: observational study - Naimova, Zilola; Mahmudova, Saodat Kurbonbekova; Khushvakova, Nilufar Jurakulovna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Sudden sensorineural hearing loss (SNHL) is considered as acute onset hearing disturbance characterized by hearing loss of greater than 30 decibels. Methods: This retrospective research included data from 83 hospitalized patients (92 ears) and was conducted in a regional multidisciplinary children's medical centre between January 2014 and December 2019. We performed examinations of the eardrum as well as cranial nerves. Results: Among the 92 ears with SNHL, 8 ears (8.7%) in age group of 2-18 years, 33 ears (35.9%) in the group of 19-30 years, 30 (32.6%) and 21 ears (22.8%) represented the age groups of 31-65 and those aged over 65 years respectively. Hearing loss in 5 ears (5,4%) was rated as light, in 7 ears (7.6%) as moderate, in 14 ears (15.2%) as severe, and 66 ears (71.7%) out of the 92 had profound degree of hearing loss. Early treatment of SNHL was positive predictive factor for recovery (OR=2.54, 95% CI 1.09-5.91, p=0.03). The presence of tinnitus was also strongly linked with better recovery outcomes while not significantly associated (OR=2.59, 95% CI 0.91-7.37, p=0.07). Conclusions: In the course of our research, we found that 11.9% of patients made a full recovery, while the total recovery rate was 42.3%. Positive prognostic markers for hearing recovery were early treatment and a strong trend was observed with the presence of tinnitus.